Vascular flora of Konün Wenu Hill (La Araucanía, Chile): composition and ecological relevance of a forest fragment in a rural–urban matrix - Pincheira-Ulbrich, Jimmy; Alvarado, Daniela; Bravo , Javiera; Antinao, Genoveva (Mediterranean Botany, 2026)
Konün Wenu Hill (38°46′ S, 72°38′ W) is a prominent insular hill of considerable historical and cultural significance, located in the Mediterranean–temperate transition of south-central Chile. It hosts a ca. 10 ha remnant of native vegetation embedded within a matrix of grasslands and Pinus radiata D. Don (Pinaceae) plantations. Through a habitat-stratified floristic inventory covering the forest interior and adjacent habitats, we recorded 158 vascular plant taxa (Tracheophyta), comprising 90 native species (including 26 Chilean endemics) and 68 alien species. The forest remnant itself contained 62 native and 17 alien species. According to national conservation assessments, the flora includes two Vulnerable species—Asplenium trilobum Cav. (Aspleniaceae) and Citronella mucronata (Ruiz & Pav.) D. Don (Cardiopteridaceae)—and one Near Threatened species, Gardoquia multiflora (Phil.) Kuntze (Lamiaceae). The richest families were Asteraceae (24 spp.), Poaceae (14), Fabaceae (11), and Rosaceae (10). Canopy species such as Cryptocarya alba (Lauraceae), typical of Mediterranean sclerophyllous forests, Nothofagus obliqua (Mirb.) Oerst. (Nothofagaceae), characteristic of south-central deciduous forests, and Eucryphia cordifolia Cav. (Cunoniaceae), a temperate evergreen element from southern Chile, co-occur in the fragment and reflect the site’s transitional biogeographic character. The surrounding grasslands contributed a suite of heliophilous elements, notably Chloraea Lindl. spp. (Orchidaceae). Isolated trees scattered throughout the grassland mosaic served as distinct microsites compared to the surrounding open areas, facilitating the establishment of species more typical of forest or shrubland environments—such as taxa associated with closed-canopy forest (e.g., Francoa appendiculata Cav.) or sclerophyllous shrubland (e.g., Myrceugenia obtusa (DC.) O. Berg). Hierarchical clustering with SIMPROF (10,000 permutations, α = 0.05) showed that local road and forestry plantation each harboured floristic compositions statistically distinct from forest, edge, and grassland—and from one another—while these latter three habitats did not differ significantly among themselves. Despite its small size and isolation, Konün Wenu supports a substantial proportion of regional plant species richness and harbours taxa of conservation concern, underscoring the ecological value of both the remnant and the microhabitat network sustained by isolated trees across the surrounding matrix.